The roles of mesenchymal stem cell-derived exosomes in diabetes mellitus and its related complications - Yang, Mengmeng; Chen, Jun; Chen, Li (Frontiers in Endocrinology, 2022)
Diabetes mellitus is a type of metabolic disease characterized by hyperglycemia, primarily caused by defects in insulin secretion, insulin action, or both. Long-term chronic hyperglycemia can lead to diabetes-related complications, causing damage, dysfunction, and failure of different organs. However, traditional insulin and oral drug therapy can only treat the symptoms but not delay the progressive failure of pancreatic beta cells or prevent the emergence of diabetic complications. Mesenchymal stem cells have received extensive attention due to their strong immunoregulatory functions and regeneration effects. Mesenchymal stem cell-derived exosomes (MSC-Exos) have been proposed as a novel treatment for diabetic patients as they have demonstrated superior efficiency to mesenchymal stem cells. This review summarizes the therapeutic effects, mechanisms, challenges, and future prospects of MSC-Exos in treating diabetes mellitus and its related complications. This review supports the potential use of MSC-Exos in future regenerative medicine to overcome the current difficulties in clinical treatment, particularly in treating diabetes.